Global organizing designs - Graen, George B.; Graen, Joni A. (LMX leadership ;, 2005)
This third volume of LMX Leadership: The Series addresses the question of how leaders prepare their teams for required loosely directed, highly coordinated, and above all, flexible operations. It is our hope that this volume will stimulate scholarly sweat, blood, and tears needed to make continued progress toward our goal of understanding how the powerful tools of relational leadership can be employed properly to create the flexible organizational structures required to compete successfully in the environmental turbulence of the 21st century. As we stated before, the rapidly changing information age is all around us and we are struggling to cope with our out-dated, rigid bureaucratic structures. The "China Price" has redefined the standards of performance world wide and they cannot be met with obsolete organizing designs.